2006
DOI: 10.1016/j.jaci.2006.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Alternaria alternata in US homes is associated with asthma symptoms

Abstract: Background-Exposure to the fungus Alternaria alternata is a risk factor for asthma. Few studies have examined Alternaria exposures in indoor environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(144 citation statements)
references
References 43 publications
(35 reference statements)
3
135
1
3
Order By: Relevance
“…SALO et al [70] could not find any association between dust-borne Alternaria alternata and physician-diagnosed asthma.…”
Section: Atopic Sensitisationmentioning
confidence: 85%
“…SALO et al [70] could not find any association between dust-borne Alternaria alternata and physician-diagnosed asthma.…”
Section: Atopic Sensitisationmentioning
confidence: 85%
“…18, 26 For Alternaria, we chose a cut point which has been associated with increased odds of asthma symptoms in the NSLAH. 27 The cut points used in the analysis were as follows: 10 μg/g for Der p 1, Der f 1, and Can f 1; 8 μg/g for Fel d 1; 8 U/g Bla g 1; 1.6 μg/g for MUP; and 7 μg/g for Alternaria.…”
Section: Discussionmentioning
confidence: 99%
“…It has first been suggested that these microorganisms could induce an allergic response, through the production of immunoglobulin (Ig)E in response to mould allergens. Allergic sensitisation to moulds, and particularly to Alternaria alternata, has indeed been associated with asthma development and severity [64][65][66][67]. However, significant associations have also been found between exposure to moulds and respiratory symptoms among nonatopic subjects [68,69].…”
Section: Mouldsmentioning
confidence: 99%